2022
DOI: 10.3389/fmicb.2022.975346
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation effects of niacin supplementation on beef cattle subjected to heat stress: A metagenomic insight

Abstract: The objective of this study was to investigate the alleviation effects of niacin supplementation on beef cattle subjected to heat stress and to provide a theoretical basis for exploring the alleviation methods of heat stress environmental factors on the rumen of beef cattle. In the experiment, 36 Jinjiang bull cattle with a body weight of about 400 ± 20.0 kg were randomly divided into three treatments, each treatment contains four replicates, with three cattle in each replicate. Treatments included thermoneutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Our result showed reduction of Desulfobacterota phylum when the dairy cows are supplemented with 200 and 400 g/d of FAF doses, indicating that these doses of FAF may create a healthier environment in the rumen and hindgut of the cows by minimizing the release of lipopolysaccharide (LPS) ( Huang et al, 2021 ). Additionally, supplementing FAF in the feed may also mitigate heat stress conditions in dairy cows ( Zou et al, 2022 ). However, further research is required to validate this potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed reduction of Desulfobacterota phylum when the dairy cows are supplemented with 200 and 400 g/d of FAF doses, indicating that these doses of FAF may create a healthier environment in the rumen and hindgut of the cows by minimizing the release of lipopolysaccharide (LPS) ( Huang et al, 2021 ). Additionally, supplementing FAF in the feed may also mitigate heat stress conditions in dairy cows ( Zou et al, 2022 ). However, further research is required to validate this potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that BR could intervene to boost the proportional abundance of advantageous bacteria to intervene in rumen microbiota disturbance and preserve the health of SFWS. Research indicates that supplementing with niacin can potentially mitigate heat stress by elevating the relative abundance of Succiniclasticum [ 44 ]. According to the majority of research, OS and heat stress are tightly related [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a coenzyme precursor, niacin has been known for its antilipolytic effect by activating the hydroxycarboxylic acid 2 receptor (HCA2), which effectively reduces the levels of all atherogenic lipoproteins including VLDL and LDL subclasses as well as Lp (a), and increases the levels of the protective lipoprotein of HDL ( Carlson, 2005 ; Pescara et al, 2010 ). Recent studies have demonstrated that the pharmacological dose of niacin did provide beneficial effects on animal health, particularly in high-yielding dairy cows under stress conditions ( Kristensen and Harmon, 2004 ; Pescara et al, 2010 ; Titgemeyer et al, 2011 ; Luo et al, 2017 , 2019 ; Zou et al, 2022 ), likely attributing to niacin’s positive influence on lipid metabolism or vasodilation ( Carlson, 2005 ; Pescara et al, 2010 ). Additionally, niacin plays important roles in converting ruminant volatile fatty acids (VFAs), such as acetate, into long-chain fatty acids ( Chilliard, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complex microbial community effectively ensures rumen fermentation in ruminants, which primarily converts feedstuffs into essential nutrients, such as VFAs, ammoniate, vitamins, and microbial proteins ( Doreau and Ottou, 1996 ; Kristensen and Harmon, 2004 ; Zou et al, 2022 ). Niacin has been proven to promote rumen microbial growth, maintain rumen microecological homeostasis, and avoid lactate accumulation in the rumen wall ( Doreau and Ottou, 1996 ; Kristensen and Harmon, 2004 ; Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation